THE NUMERICAL METHODS FOR SOLVING NONLINEAR INTEGRAL EQUATIONS - Radi, Abdel; Elgasim Msis, Marwa Eltayb Abu (IJRDO -JOURNAL OF MATHEMATICS, 2023)
Volterra integral equations are a special type of integrative equations; they are divided into two categories referred to as the first and second type. This thesis will deal with the second type which has wide range of the applications in physics and engineering problems. The aim of this paper is to compare between analytical solution and numerical solution to solve Integral Equations. Numerical examples are presented to illustrate the applications of this methods and to compare the computed results with other numerical methods for analytical solutions. Finally by comparison of numerical results, Simplicity and efficiency of this method be shown.